PERAN TOKOH AGAMA DALAM MENANAMKAN AKHLAKUL KARIMAH PADA MASYARAKAT NELAYAN DI KABUPATEN PROBOLINGGO - Hani Nafi'ah Rachmawati; Khadavi, Muhammad Jadid (LPPM STAI Muhammadiyah Probolinggo, 2023)
The aim of this research is to analyze the role of religious figures in instilling good morals in the fishing community in Tongas Wetan Village, Tongas District, Probolinggo Regency. Religious figures have a very important role in guiding and providing direction to the community so that they always behave well and avoid inappropriate behavior. The research approach used in this research is qualitative with a case study type of research. Research informants include: religious leaders, community leaders, and residents. The results of the research show that the role of religious figures in instilling morals in the fishing community of Tongas Wetan Village is as leaders, role models (uswah hasanah), and guides (mentors). Being a leader means not only leading congregational prayers but also providing spiritual and social guidance. Being a role model means being able to become a figure and moral guide for society who reflects religious values ​​in daily actions. Being a mentor means actively providing guidance in religious and social activities and implementing Islamic teachings. The form of instilling good morals is through being active in religious and social activities in the community. Keywords: Religious Leaders; Good Moral; Fishermen Community.